2017
DOI: 10.5194/npg-24-343-2017
|View full text |Cite
|
Sign up to set email alerts
|

Generation and propagation of stick-slip waves over a fault with rate-independent friction

Abstract: Abstract. Stick-slip sliding is observed at various scales in fault sliding and the accompanied seismic events. It is conventionally assumed that the mechanism of stick-slip over geo-materials lies in the rate dependence of friction. However, the movement resembling the stick-slip could be associated with elastic oscillations of the rock around the fault, which occurs irrespective of the rate properties of the friction. In order to investigate this mechanism, two simple models are considered in this paper: a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…Laboratory experiments show that fault structural and strength inhomogeneity (Benioff & Byerlee, ; Ben‐Zion, ) and rate‐ and state‐dependent friction (McLaskey & Lockner, ) can be the origin of strong stick‐slip behaviors in real earthquakes. Karachevtseva et al () and Matsukawa and Saito () used Burridge‐Knopoff model (Burridge & Knopoff, ) and confirmed the occurrence of stick‐slip in a rate‐independent friction model due to the initial stress heterogeneity, similar to the case in this paper. The cause of this type of slip‐stick behavior is the elastic oscillations of the rock surrounding the fault after a slip on each element.…”
Section: Large‐scale Rupture Modelsupporting
confidence: 86%
“…Laboratory experiments show that fault structural and strength inhomogeneity (Benioff & Byerlee, ; Ben‐Zion, ) and rate‐ and state‐dependent friction (McLaskey & Lockner, ) can be the origin of strong stick‐slip behaviors in real earthquakes. Karachevtseva et al () and Matsukawa and Saito () used Burridge‐Knopoff model (Burridge & Knopoff, ) and confirmed the occurrence of stick‐slip in a rate‐independent friction model due to the initial stress heterogeneity, similar to the case in this paper. The cause of this type of slip‐stick behavior is the elastic oscillations of the rock surrounding the fault after a slip on each element.…”
Section: Large‐scale Rupture Modelsupporting
confidence: 86%
“…In the absence of slippage, the friction force takes on some values, generally speaking, not the same at different points of the plate, but not exceeding the absolute value of the limit. In the problem under consideration, as well as in [1][2][3][4][5][6], we will consider the limiting friction force to be constant. In the case when h is small compared to the characteristic propagation length of the elastic pulse, the stress change over the thickness of the plate can be neglected and the friction force can be considered as a volumetric one with density η = f N/h.…”
Section: Setting Of the Boundary Value Problemmentioning
confidence: 99%
“…Elastic wave propagation in a cylindrical body in the presence of Coulomb friction on the contact surface with another nondeformable body and induced by the propagating wave parameters is considered in [4]. It is shown that the accumulation of elastic energy in sliding plates on both sides of the fault can cause fluctuations in the sliding velocity, even with constant friction [5]. The authors of [6] study the problem of longitudinal wave propagation in an elastic rod attached to a locally damaged foundation through a thin elastic layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of slippage, the friction force takes on some values, generally speaking, not the same at different points of the plate, but not exceeding the absolute value of the limit. In the problem under consideration, as well as in [1][2][3][4][5][6], we will consider the longitudinal friction force to be constant. In the case when h is small compared to the characteristic propagation length of the elastic pulse, the stress change over the thickness of the plate can be neglected and the friction force can be considered as volumetric one with density fNh η = .…”
Section: Setting Of the Boundary Value Problemmentioning
confidence: 99%
“…Elastic wave propagation in a cylindrical body in the presence of Coulomb friction on the contact surface with other nondeformable body and induced by the propagating wave parameters is considered in [4]. It is shown that the accumulation of elastic energy in sliding plates on both sides of the fault can cause fluctuations in the sliding velocity even with constant friction [5]. The authors of 2 [6] study the problem of longitudinal waves propagation in an elastic rod attached to a locally damaged foundation through a thin elastic layer.…”
Section: Introductionmentioning
confidence: 99%